Kinetics of photoinduced birefringence in the guest-host system of poly(methyl methacrylate) doped with azobenzene-containing crown ethers - Shimizu, Flavio Makoto; Volpati, Diogo; Giacometti, Jose Alberto; Sworakowski, Juliusz; Janus, Krzysztof; Luboch, Elzbieta (Wiley-Blackwell, 2007)
The kinetics of the buildup and decay of photoinduced birefringence was examined in a series of host-guest systems: azobenzene-containing crown ethers, differing in the size of the crowns, dissolved in a poly (methyl methacrylate) matrix. In all samples, the kinetics of the buildup of the birefringence was reasonably described by a sum of two exponential functions, the time constants being inversely proportional to the intensity of the pumping light and the magnitudes of the signals at the saturation level depending on the pumping light intensity and sample thickness. The dark decays were best described by the stretched exponential function, with the characteristic parameters (time constant and stretch coefficient) being practically independent of the type of crown ether. The time constants of the signal decay were orders of magnitude shorter than the respective constants of the dark isomerization of the azo crown ethers, thus indicating that the process controlling the decay was a relaxation of the polymer matrix and/or a rearrangement of the flexible parts of the crowns. (C) 2007 Wiley Periodicals, Inc.
Keywords: host-guest systems; optics; photochemistry